Identifying opportunities to improve management of water stress in banana production - Panigrahi, Niranjan; Thompson, Andrew J.; Zubelzu, Sergio; Knox, Jerry W. (Elsevier, 2020)
Banana (Musa spp.) is one of the most valuable global agricultural commodities, with commercial plantations responsible for supplying nearly 15 % of total global banana production. These plantations are underpinned by major infrastructural investments and a high dependence on fertilizer, pesticide and irrigation inputs. In contrast, smallholders and subsistence farmers often cultivate bananas for local markets with minimal inputs. Water stress due to increasing rainfall variability and competition for water resources are emerging as major production constraints for both commercial and smallholder production. Water stress-induced yield losses of up to 65 % have been reported due to loss in bunch weight even in moderate to low rainfall areas. Thus, investments in more efficient irrigation systems and water-saving technologies are being widely promoted to increase water productivity through improved scheduling to reduce drainage and runoff losses. This paper synthesises scientific and industry evidence on crop growth and development including root and shoot development, plant water relations, and yield response to water. It also critiques the importance of irrigation scheduling for maximising irrigation efficiency. New evidence to support the synchronization of irrigation with crop water demand to reduce environmental impacts is provided. High variability in crop water demand (1200–2690 mm per year) was found to be linked to cultivar choice, crop development cycle, and fluctuating conditions in environmental and edaphic factors. The findings confirm that irrigation should be scheduled at moderate levels of soil water deficit sufficient to promote deep and extensive rooting while maintaining banana quality. Management practices are recommended to mitigate water stress without compromising yield under limited rainfall and irrigation conditions. The ratooning cycle of banana also affects rooting activity and crop coefficients (Kc) compared to other annual crops. These aspects need to be considered when improving irrigation and crop modelling for banana. The findings provide valuable new insights and evidence for scientists and practitioners involved in banana research and management.
Keywords: Agriculture; Irrigation; Scheduling; Soil management; Yield